AN OVERVIEW ON BLOOM'S REVISED TAKSONOMY - Ömer Tutkun (Sakarya University Journal of Education)
In this study, the main purpose is to present the main frame of revised version in 2001 of Bloom's taxonomy that has been accepted extensively in our country since 1956 as well as around the world. In accordance with this purpose, in the study, answers have been searched to these questions: 1- The rise of the original Bloom's taxonomy and what are the key features of? 2- What are the reasons for renewal of original taxonomy? 3- What kind of arrangements has been made in revised taxonomy? 4- What are the comments on Revised Taxonomy? Scanning method was used as a research method. These are the findings that were acquired in line with the research questions: 1- Between 1948-1956, a group of educators under the coordination of Bloom, developed the classification of cognitive domain. 2- Being modified of thinking and practices related with education by changes since 1956 is the leading motive of the taxonomy's being revised. 3- In revised taxonomy, two different dimensions revealed including dimension of information and dimension of the cognitive process. 4- Dimension of information is similar to the lower stages of knowledge digit of original taxonomy. Cognitive process dimension refers to the action size of the gains.